The guardians of Island X - Delaney, Rachelle (The Ship of Lost Souls ;, 2012)
A month after twelve-year-old Scarlet brought her crew, The Lost Souls, to mysterious Island X to guard a great treasure, they must face both the King's Men and pirates, unsure if they can defend themselves on land as well as they did at sea.